In My Nicaraguan High School: Giving Excluded Women and Men a Second Chance - Gullette, Margaret Morganroth (Radical Teacher, 2017)
When I went to Nicaragua for the first time during the Contra war, I had no idea that I would soon wind up helping a Nica friend start two literacy programs and then a Free High School for Adults. It opened in 2002, and now, only 15 years later, we have 1001 graduates, 54% women, 45% rural (mainly from subsistence farm families)–all of them excluded from the regular high schools for one reason or another: being pregnant, being a woman, turning eighteen, working five days a week, or living too far from town without the ability to pay bus fare. My real education came with theirs and is still going on, with no end in sight. What I wanted to know was how the teachers–all college graduates who were teaching in the high prestige regular high schools–figured out how to teach these people, many of whom had been out of school for decades and were unused to learning or scholastic discipline; many accustomed to being heads of households; some pregnant or carrying a baby to School for lack of child care or need to nurse; some drunk or exhausted early on Saturday mornings when classes began. The teachers told me their own stories, of overcoming prejudice and learning how to create a welcoming atmosphere. And the graduates told me THEIR stories, of what it took to succeed in those conditions, and how education–especially learning how to speak better– transformed them, and they, in turn, transformed the entire culture and economy of the region.